IMPLEMENTASI METODE GALLERY WALK DALAM PEMBELAJARAN PAIBP UNTUK MENINGKATKAN KOLABORATIF PESERTA DIDIK SMKN 2 BLORA - Jamilah, Siti; Syaifulloh, Ahmad; Nurkayati, Siti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Islamic Religious Education and Character (PAIBP) plays an important role in building students' character and morals. In responding to the challenges of the 21st century, which require critical thinking, communication, collaboration, and creativity skills (4C), innovative learning methods are needed to foster students' social and emotional attitudes. One effective method is the Gallery Walk, which encourages students to work together in groups, present their work, and interact actively with one another. This study aims to describe the implementation of the Gallery Walk method in PAIBP learning and its impact on the collaborative abilities of XI MPLB II students at SMK Negeri 2 Blora. The method used is descriptive qualitative with data collection through observation, interviews, and documentation that are analyzed interactively. The research results indicate that Gallery Walk is quite effective in enhancing students' collaborative abilities, as evidenced by increased engagement in discussions, mutual respect, and the ability to give and receive feedback. Furthermore, this method also strengthens students' understanding of PAIBP material and supports the development of Islamic character, including tolerance, responsibility, and social care. Therefore, Gallery Walk is an appropriate alternative strategy for PAIBP learning, aligned with the demands of 21st-century skills and supporting cooperative learning theory based on social interaction. The use of this method is expected to facilitate more effective learning and have a positive impact on students' character. ABSTRAK Pendidikan Agama Islam dan Budi Pekerti (PAIBP) berperan penting dalam membentuk akhlak dan karakter peserta didik. Menghadapi tantangan abad ke-21 yang menuntut keterampilan berpikir kritis, komunikasi, kolaborasi, dan kreativitas (4C), diperlukan metode pembelajaran inovatif yang menumbuhkan sikap sosial dan emosional. Salah satu metode yang relevan adalah Gallery Walk, di mana siswa bekerja dalam kelompok, menyajikan karya dalam bentuk galeri, dan berinteraksi secara aktif. Penelitian ini bertujuan untuk mendeskripsikan implementasi Gallery Walk dalam pembelajaran PAIBP dan dampaknya terhadap kemampuan kolaboratif peserta didik kelas XI MPLB II SMK Negeri 2 Blora. Menggunakan pendekatan kualitatif deskriptif, data diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis secara interaktif. Hasil penelitian menunjukkan bahwa Gallery Walk efektif dalam meningkatkan kemampuan kolaboratif siswa, dengan peningkatan keterlibatan dalam diskusi, sikap saling menghargai, dan kesediaan untuk memberi serta menerima umpan balik. Selain memperkuat pemahaman materi PAIBP, metode ini berkontribusi pada pembentukan karakter Islami yang meliputi toleransi, tanggung jawab, dan kepedulian sosial. Dengan demikian, Gallery Walk merupakan alternatif strategi pembelajaran PAIBP yang selaras dengan tuntutan keterampilan abad ke-21 dan mendukung teori pembelajaran kooperatif berbasis interaksi sosial.